The Impact of Procedural Asymmetry in Games of Imperfect Information - Nadine Chlaß (Verein für Socialpolitik, 2010)
Games of imperfect information distribute information unevenly amongst parties. Recently, parties have been claimed to hold preferences purely over such procedural aspects. Here, I explore the impact purely procedural preferences exert if agents are without influence on the procedure itself. I design a game of imperfect information which exhibits extreme procedural asymmetry in that several procedural aspects advantage one and the same party over another. In an experimental test, parties are found to monetarily compensate the asymmetry such that almost no winner's curse results. I explain the compensation by an instrument for purely procedural preferences (Chlaß et al. 2009). The residual winner's curse links to personality traits. The game abstracts a management buy-in, the natural counterpart to a management buy-out.
Keywords: C78; D63; D82; 330; procedural preferences; asymmetric information; winner's curse